Immune Repertoire after Immunization As Seen by Next-Generation Sequencing and Proteomics - VanDuijn, Martijn M.; Dekker, Lennard J.; van IJcken, Wilfred F. J.; Sillevis Smitt, Peter A. E.; Luider, Theo M. (Frontiers in Immunology, 2017)
The immune system produces a diverse repertoire of immunoglobulins in response to foreign antigens. During B-cell development, VDJ recombination and somatic mutations generate diversity, whereas selection processes remove it. Using both proteomic and NGS approaches, we characterized the immune repertoires in groups of rats after immunization with purified antigens. Proteomics and NGS data on the repertoire are in qualitative agreement, but did show quantitative differences that may relate to differences between the biological niches that were sampled for these approaches. Both methods contributed complementary information in the characterization of the immune repertoire. It was found that the immune repertoires resulting from each antigen had many similarities that allowed samples to cluster together, and that mutated immunoglobulin peptides were shared among animals with a response to the same antigen significantly more than for different antigens. However, the number of shared sequences decreased in a log-linear fashion relative to the number of animals that share them, which may affect future applications. A phylogenetic analysis on the NGS reads showed that reads from different individuals immunized with the same antigen populated distinct branches of the phylogram, an indication that the repertoire had converged. Also, similar mutation patterns were found in branches of the phylogenetic tree that were associated with antigen-specific immunoglobulins through proteomics data. Thus, data from different analysis methods and different experimental platforms show that the immunoglobulin repertoires of immunized animals have overlapping and converging features. With additional research, this may enable interesting applications in biotechnology and clinical diagnostics.